A study on the level of knowledge in identifying warning signs of cancer / Jalwaty Jamalul , Nur Alia Izati Abdullah and Nur Syazana Huda Ramle - Jamalul, Jalwaty; Abdullah, Nur Alia Izati; Ramle, Nur Syazana Huda (2018)
Cancer can be defined as an uncontrolled growth of cell in human body and it is can be diagnosed in all level of age, races and also both genders. Increased awareness and high knowledge of warning signs of cancer might have great impact on the disease. This study has been done to determine the level of knowledge in identifying warning signs of cancer among students in UiTM Kota Bharu Campus and to examine the factors that contribute significantly to the level of knowledge. There are about 205 questionnaires has been distributed through WhatsApp application and simple random sampling are used as the sampling technique. The findings shows that most of the respondents have low level of knowledge (84.9%). Binary logistic regression analysis was performed to identify the significant factors that contribute to the level of knowledge in identifying warning signs of cancer. Overall, there were two significant variables (family monthly income and family history of having cancer) found in logistic regression analysis. There are several recommendations highlighted in this study such as the strategies to communicate the warning signs of cancer to the public